Development of Android-Based Software to Support The Selection of University Majors that Fits with Student Personality Type - Fridayanti Fridayanti; Wisnu Uriawan; Aldy Rialdy Atmadja (Universitas Muhammadiyah Malang, 2018)
Selecting study program is important things that must decide for high school student in Indonesia. However, students often have difficulties to explore the field of study which match with him. Technology can be used as a tool for making a decision, for example by using android application. Android platform has advantages because it is easy to accessible and familiar in teenagers in Indonesia. In this research, an application was developed by Rational Unified Process methodology. The selection of study program is done with knowing personality type. There are 6 criteria in defining personality type with RIASEC method: Realistic, Investigative, Artistic, Social, Enterprising, Conventional. Personality type can be known after user filled the questionnaire in an application. Next, an application can display study program that matches the type of user personality. From evaluation and analysis, the result showed that application is easy to use. It is expected that this application can be a simulated application which provides information and solutions in advance to selecting study program in universities.